Measures of mortality in COVID-19: beyond the death toll - Prasad Chathuranga Weerasinghe; Indumini Gunatilake; Nirma Alpitiarachchi; Indika Gunawardana; Ahmed Shiyam; Suwani Dasanayake; Gayani Dissanayake; Thanuja Rathnayake; Irshad Mashood; Disala Welgama; Jinadari Amarasena; Iresha Jayawickrama; et al. (College of Community Physicians of Sri Lanka, 2020)
No abstract available